AI based Mobile Application for Waste Management and Recycling - Maharjan, Ojaswi (MVIC Journal of Management and Information Technology, 2025)
Waste disposal is one of the challenges faced by most developing countries. People follow improper waste disposal practices by throwing all the waste into the landfill sites. This research introduces a mobile application integrating Artificial Intelligence (AI) to classify waste image types of recyclable objects and suggest recycling tips. It also provides a platform to schedule organic waste pickup service. It uses a lightweight MobileNetV2 model to identify the waste types. Gamification techniques, such as a point-based reward system, are developed for user engagement in the application. This research paper contributes to the growing positive use of AI in the environmental sustainability sector.